Palliative care: views of patients and their families. - Higginson, I (1990)
OBJECTIVE--To investigate the current problems and needs of terminally ill cancer patients and their family members, and to discover their views of hospital, community, and support team services. DESIGN--Prospective study of patients and families by questionnaire interviews in the patients' homes. SETTING--Inner London and north Kent (London suburbs). SUBJECTS--65 Patients, each with a member of their family or a career. MAIN OUTCOME MEASURES--Ratings of eight current problems and ratings and comments on three services-hospital doctors and nurses, general practitioners and district nurses, and the support team staff-obtained after a minimum of two weeks' care from palliative care support teams. RESULTS--Effect of anxiety on the patient's nearest career. and symptom control were rated as the most severe current problems by both patients and families; a few patients and families identified other severe problems. Families' ratings of pain control, symptom control, and effect of anxiety on the patient were significantly worse than the patients' ratings (p less than 0.05). Support teams received the most praise, being rated by 58 (89%) patients and 59 (91%) of family members as good as excellent. General practitioners and district nurses were rated good or excellent by 46 (71%) patients and 46 (71%) family members, but six (9%) in each group rated the service as poor or very bad, and ratings in the inner London district were significantly worse than those in the outer London district. Hospital doctors and nurses were rated good or excellent by 22 (34%) patients and 35 (54%) of family members, and 14 (22%) patients and 15 (23%) family members rated this service as poor or very bad. Negative comments referred to communication (especially at diagnosis), coordination of services, the attitude of the doctor, delays in diagnosis, and difficulties in getting doctors to visit at home. Family members were more satisfied with the services than were patients. CONCLUSIONS--Palliative care needs to include both the patient and family because the needs of the family may exceed those of the patient. Support teams and some hospital and community doctors and nurses met the perceived needs of dying patients and families, but better education and organisation of services are needed.